Performance Analyses of MRT/MRC in NOMA Full-Duplex Relay Networks With Residual Hardware Impairments - Toka, Mesut; Guven, Eray; Kurt, Gunes Karabulut; Kucur, Oğuz (IEEE-Inst Electrical Electronics Engineers Inc, 2025)
This paper analyzes the performance of maximum-ratio transmission (MRT)/maximum-ratio combining (MRC) scheme in a dual-hop non-orthogonal multiple access (NOMA) full-duplex (FD) relay networks in the presence of residual hardware impairments (RHIs). The effects of channel estimation errors (CEEs) and imperfect successive interference cancellation are also considered to deal with a more realistic scenario. In the network, the base station and multiple users utilize MRT and MRC, respectively, while a dedicated relay operates in amplify-and-forward mode. Exact outage probability (OP) expression is derived for Nakagami-$m$ fading channels. Furthermore, tight lower bound and asymptotic expressions are also derived to provide further insights in terms of diversity order and array gain. The investigated network has been compared to half-duplex (HD)-NOMA and FD-orthogonal multiple access counterparts. The analytical results validated by simulations and test-bed implementations (by using software defined radios) demonstrate the importance of loop-interference cancellation process in the FD relay for the investigated system to perform better than HD-NOMA counterpart. Also, a performance trade-off between the MRT and MRC schemes is observed under CEE effects among users. Furthermore, it is shown that RHIs have a significant effect on the performance of users with lower power coefficients, however it does not change the diversity order. RHIs and CEEs have the most and least deterioration effects on the system performance, respectively.
Keywords: NOMA; Relays; Fading channels; MIMO; Hardware; Transmitting antennas; Full-duplex system; Channel estimation; Vectors; System performance; Channel estimation error; full-duplex relay; imperfect successive interference cancellation; MIMO-NOMA; residual hardware impairments